Role of the government in social capital development in Indonesia - BAKRI PUTRA, A.; SURAJI, M.; EMBI, M.A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Social capital development is now the main strategy for social and economic development in Indonesia. This focus is expected to enhance the capacity of the nation. However, the development of social capital in most Indonesian regions is still considered inadequate. Previous research found a lack of trust in society in most regions in Indonesia. Other studies found that inadequate social capital had caused problems related to insecurity and drug abuse in some regions. These insecurity issues have given rise to other problems, such as poverty, decreasing levels of health, and anxiety.RESUMEN El desarrollo del capital social es ahora la principal estrategia para el desarrollo social y económico en Indonesia. Se espera que este enfoque mejore la capacidad de la nación. Sin embargo, el desarrollo del capital social en la mayoría de las regiones de Indonesia todavía se considera inadecuado. Otros estudios encontraron que el capital social inadecuado había causado problemas relacionados con la inseguridad y el abuso de drogas en algunas regiones. Estos problemas de inseguridad han dado lugar a otros problemas, como la pobreza, la disminución de los niveles de salud y la ansiedad.